Znaczenie włosów w obrzędach żałobnych wybranych kultur antycznych: grecko-rzymskiej i egipskiej - Liwoch, Beata (Załącznik Kulturoznawczy, 2023)
Hair carried a significant symbolic value among the cultures of ancient Greece, Rome and Egypt. In this article I analyse the connection between hair and funeral customs, ceremonies and the mourning. Firstly I discuss Greek and Roman rituals. Subsequently I try to confront mentioned notions with Egyptian culture. Main rituals that undergo comparison are: shaving, cutting, growing and letting hair loose. I also try to explain these ceremonial gestures. In the analysis that I carried out I use examples of literary nature as well as historic ones